Appropriately framing maternal request caesarean section - Romanis, Elizabeth Chloe (Journal of medical ethics, 2022)
In their paper, ‘How to reach trustworthy decisions for caesarean sections on maternal request: a call for beneficial power’, Eide and Bærøe present maternal request caesarean sections (MRCS) as a site of conflict in obstetrics because birthing people are seeking access to a treatment ‘without any anticipated medical benefit’. While I agree with the conclusions of their paper -that there is a need to reform the approach to MRCS counselling to ensure that the structural vulnerability of pregnant people making birth decisions is addressed—I disagree with the framing of MRCS as having ‘no anticipated medical benefit’. I argue that MRCS is often inappropriately presented as unduly risky,without supporting empirical evidence,and that MRCS is most often sought by birthing people on the basis of a clinical need. I argue that there needs to be open conversation and frank willingness to acknowledge the values that are currently underpinning the presentation of MRCS as ‘clinically unnecessary’; specifically there needs to be more discussion of where and why the benefits of MRCS that are recognised by individual birthing people are not recognised by clinicians. This is important to ensure access to MRCS for birthing people that need it.